2020
DOI: 10.18502/jovr.v15i1.5934
|View full text |Cite
|
Sign up to set email alerts
|

Fourier Analysis of Keratometric Data in Epithelium Removal versus Epithelial Disruption Corneal Cross-linking

Abstract: Purpose: To compare epithelium-removal and epithelium-disruption corneal crosslinking (CXL) methods in Fourier analysis of keratometric data and clinical outcomes. Methods: In this double-masked randomized clinical trial, each eye of 34 patients with bilateral keratoconus was randomly allocated to either the epithelium-removal or epithelium-disruption CXL treatment groups. Ocular examination, refraction, uncorrected and best spectacle-corrected visual acuity (UCVA and BSCVA, respectively) measurements, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…P), and irregularity (I), provides information on the 3D shape of the cornea and offers more comprehensive assessment of the cornea compared with mean keratometric values. 6 Many studies have reported on tomographic parameters in healthy adults 7,8 ; however, data in children are scarce. Because of the lack of normative values of BAD, it is not uniformly defined who should be tomographically monitored for KC development in pediatric population.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…P), and irregularity (I), provides information on the 3D shape of the cornea and offers more comprehensive assessment of the cornea compared with mean keratometric values. 6 Many studies have reported on tomographic parameters in healthy adults 7,8 ; however, data in children are scarce. Because of the lack of normative values of BAD, it is not uniformly defined who should be tomographically monitored for KC development in pediatric population.…”
mentioning
confidence: 99%
“…P), and irregularity (I), provides information on the 3D shape of the cornea and offers more comprehensive assessment of the cornea compared with mean keratometric values. 6…”
mentioning
confidence: 99%